2008
DOI: 10.1292/jvms.70.873
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Production and Foodborne Diseases from Food Animals in Thailand

Abstract: ABSTRACT. Thailand is a developing nation dependent on agriculture. Due to lack of modern public health practices, she suffers from the consequences of foodborne illnesses. The number of foodborne infection cases has nearly doubled in the past 10 years. Salmonella and Campylobacter pose the greatest risk of bacterial contaminants, mostly from pigs and chickens, and this paper will review livestock production systems and foodborne diseases from cases stemming from these sources. Due to the complexity of the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Farmers, abattoir workers and food handlers as well as consumers are thus the large number of people directly at risk of acquiring antibiotic-resistant bacteria via the food chain. In the developing world, where biosecurity and food safety measures are limited along the farm-to-fork continuum and where humans interact intimately with animals and the environment, the public health risk is likely to be associated with both the direct and indirect transmission of antibiotic-resistant bacteria and ARGs (Padungtod et al, 2008). In contrast, in developed countries, the indirect contamination seems to be more prevalent as antibiotic-resistant bacteria and ARGs emerging on-farms, are maintained throughout the food production and contaminated food products reach the end consumers to create foodborne infections (EFSA and ECDC, 2015).…”
Section: Transmission Routes Of Antibiotic Resistance Along the Food mentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers, abattoir workers and food handlers as well as consumers are thus the large number of people directly at risk of acquiring antibiotic-resistant bacteria via the food chain. In the developing world, where biosecurity and food safety measures are limited along the farm-to-fork continuum and where humans interact intimately with animals and the environment, the public health risk is likely to be associated with both the direct and indirect transmission of antibiotic-resistant bacteria and ARGs (Padungtod et al, 2008). In contrast, in developed countries, the indirect contamination seems to be more prevalent as antibiotic-resistant bacteria and ARGs emerging on-farms, are maintained throughout the food production and contaminated food products reach the end consumers to create foodborne infections (EFSA and ECDC, 2015).…”
Section: Transmission Routes Of Antibiotic Resistance Along the Food mentioning
confidence: 99%
“…In Thailand, high levels of ESBL-producing Salmonella Typhimurium in poultry (77.3%) and pigs (40.4%) were reported, with an overall 86% prevalence of MDR (Padungtod et al, 2008). In the same country, Boonyasiri et al (2014) identified elevated prevalence of ESBL-producing E. coli in the food chain during the years 2012–2013, these being 77% in pigs, 40% in poultry, 77% in farmers, 76% in food handlers, 61% in pork, and 50% in chicken.…”
Section: Current Status Of Antibiotic Resistance In the Food Chainmentioning
confidence: 99%
“…The entry of Salmonella carrier pigs into slaughterhouses is a major source of meat contamination and of introduction of Salmonella into the food chain (McDowell et al, 2007;Käsbohrer et al, 2000;Berends et al, 1997;Padungtod et al, 2008;Padungtod et al, 2006). For this reason, several studies have investigated the Salmonella prevalence from the feces of pigs in slaughterhouses and farms (Käsbohrer et al, 2000;Lomonaco et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are a major reservoir of bacterial zoonotic pathogens such as Salmonella (McDowell et al, 2007;Käsbohrer et al, 2000;Mainar-Jaime et al, 2008;Lomonaco et al, 2009), Campylobacter (Padungtod et al, 2008;Denis et al, 2009) and Escherichia coli (Teshager et al, 2000). Except for self-consumption and scientific *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this system, all pigs should enter and leave from the facility together at the same time and this should be applied in mating, farrowing, and nursery units. This system can help to reduce the risk of Salmonella infection since the pigs raised under the same management system are considered to have a similar disease status (Scott et al, 2006;Padungtod et al, 2008).…”
Section: Managementmentioning
confidence: 99%